A topological and domain theoretical study of total computable functions - Olguin, Cláudio Andrés Callejas (2016)
Topologically the set of total computable functions has been studied only as a subspace of a Baire space. Where the topology of this Baire space is the induced topology of a Scott topology for the partial functions (not necessarily computable). In this thesis a novel topology on the index set of the set of total computable functions is built and proved that it is not homeomorphic to the aforementioned subspace of the presented Baire space. There is an important undecidable subset of the set of total computable functions called the set of regular computable functions that receives particular attention in this thesis. In order to make a topological study of this set a whole theoretical apparatus is constructed. After presenting the state of the art of generalised domain theory, a novel generalisation of algebraic domains coined as algebraic quasidomains is introduced. With a suited partial-order an algebraic quasi-domain is built for the set of total computable functions. Through the Scott topology associated with this algebraic quasi-domain a necessary condition for the regular computable functions is obtained. It is proved that this later topology is not homeomorphic to the previously mentioned subspace of the presented Baire space. As a byproduct a Scott topology for the set of total functions (not necessarily computable) is introduced. It is proved that this later topology is not homeomorphic to the presented Baire space. It is also proved that the Scott topologies in the set of total functions and in the subset of total computable functions have the set of total functions with finite support as a common dense set. Analogously it is proved that the topology in the index set of the set of total computable functions has as a dense set the indexes corresponding to a computable enumeration without repetition of the set of total functions with finite support.